2010
DOI: 10.5004/dwt.2010.1034
|View full text |Cite|
|
Sign up to set email alerts
|

Treatment of combined bleaching effluent by membrane filtration technology for system closure in paper industry

Abstract: A B S T R A C TThis study has been carried out for the treatment of combined bleaching effluent of an Indian pulp and paper mill. The Chlorination, extraction, Hypo-1 & Hypo-2 (CEHH) sequence is being used for the bleaching of hardwood pulp in the mill. Effluent was treated by the Ultrafiltration (UF), Nanofiltration (NF) and Reverse Osmosis (RO). Thin film composite spiral-wound modules, having crass flow membranes made-up by polysulphone and polyamide were used in the study. Three initial inlet pressures wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Membrane filtration at low pressure is reported to be best for bleach effluent treatment in pulp and paper mills [ 23 ]. Likewise, it has also been reported that the performance of using RO in the reduction in pulp and paper industry effluent is higher than UF and nanofiltration [ 24 ]. In addition, the authors of [ 25 ] have recommended the combined RO-UF membrane process for the treatment of wastewater.…”
Section: Resultsmentioning
confidence: 99%
“…Membrane filtration at low pressure is reported to be best for bleach effluent treatment in pulp and paper mills [ 23 ]. Likewise, it has also been reported that the performance of using RO in the reduction in pulp and paper industry effluent is higher than UF and nanofiltration [ 24 ]. In addition, the authors of [ 25 ] have recommended the combined RO-UF membrane process for the treatment of wastewater.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of the RO unit, however, resulted in the total degradation of COD, lignin, and color at a pH of 5.74 . In a study by Shukla et al, when combined acidic and alkaline bleaching wastewaters were fed to the RO feed side, the removal of color was greater than COD. Even though RO does not require chemicals or thermal energy and can be used for tertiary treatment applications, it is not recommended to use RO directly for highly contaminated wastewater since higher levels of COD and lignin adversely affect the quality of the permeate.…”
Section: Physical and Chemical-based Treatmentmentioning
confidence: 98%